Stitched up : the anti-capitalist book of fashion - Hoskins, Tansy E. (Counterfire (Series), 2014)
Combining industry insider interviews with a fascinating historical narrative, Stitched Up delves into the alluring world of fashion to reveal what is behind the clothes we wear. Moving between Karl Largerfeld and Karl Marx, Stitched Up explores consumerism, class and advertising to reveal the interests which benefit from exploitation. Tansy E. Hoskins dissects fashion's vampiric relationship with the planet and with our bodies to uncover what makes it so damaging. Why does 'size zero' exist and what is the reality of working life for models? In a critique of the portrayal of race in fashion, Stitched Up also examines the global balance of power in the industry. In a compelling conclusion Stitched Up explores the use of clothing to resist. Can you shock an industry that loves to shock? Is 'green fashion' an alternative? Stitched Up provides a unique critical examination of contemporary culture and the distorting priorities of capitalism.